2016
DOI: 10.1111/liv.13195
|View full text |Cite
|
Sign up to set email alerts
|

The impact of infection by multidrug‐resistant agents in patients with cirrhosis. A multicenter prospective study

Abstract: Infection by MDRA is frequent in patients with cirrhosis and the prognosis is severe, especially in patients unresponsive to empiric antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 50 publications
7
68
0
1
Order By: Relevance
“…The global spread of multidrug‐resistant bacteria is attracting scientific attention in recent years . However, less attention has been paid on the impact of colonisation and infection caused by CRGN in patients with liver diseases and especially in cirrhotic patients . Cirrhotic patients are frequently exposed to antibiotic selective pressure, which has been identified to promote the occurrence of multidrug‐resistance .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The global spread of multidrug‐resistant bacteria is attracting scientific attention in recent years . However, less attention has been paid on the impact of colonisation and infection caused by CRGN in patients with liver diseases and especially in cirrhotic patients . Cirrhotic patients are frequently exposed to antibiotic selective pressure, which has been identified to promote the occurrence of multidrug‐resistance .…”
Section: Discussionmentioning
confidence: 99%
“…Independently from limitations in antibiotic treatment driven by resistance pattern, the cirrhotic patients’ outcome might further be afflicted by various non‐specific immune abnormalities, for example, macrophage dysfunctions, which have been described to increase the patients’ susceptibility to bacterial infections . Inflammatory stimuli, which lead to a shift in gut microbiota towards facultative anaerobic or aerobic species, might therefore favour the spread of (multidrug‐resistant) Enterobactericeae , P. aeruginosa , A. baumannii or S. maltophilia from one reservoir to another, for example, the respiratory or urinary tract . Considering our data, outcome of patients tested positive for Enterobacteriaceae is slightly better than the outcome of patients tested positive for non‐fermenting CRGN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This single‐center study demonstrated the prognostic role of BI in LT candidates. Previous studies already showed the burden of BI on the natural history of cirrhosis, due to the related risk of further liver decompensation, multiorgan involvement, and mortality . BI is particularly important for patients listed for LT, who are at the highest risk of developing infection as a result of more severely decompensated liver disease, more frequent contact with health care facilities, and invasive procedures …”
Section: Discussionmentioning
confidence: 99%
“…BIs were diagnosed using the following criteria: Bloodstream infection: positive blood cultures in the absence of any recognized source of infection. Pneumonia: evidence on X‐ray or CT scan of pulmonary infiltration associated with other typical signs (fever, dyspnea, cough, pleural chest pain, or signs of consolidation on physical examination). Spontaneous bacterial peritonitis (SBP) or spontaneous empyema: indicated by a polymorphonuclear cell count >250/mm 3 in ascitic fluid, for which the available guidelines were used for diagnosis and management Urinary tract infection (UTI): symptoms suggestive of UTI and confirmatory urine leucocyte count >15 cells per high‐power field and/or positive urine culture. Soft tissue infection: fever and clinical signs of cellulitis. Infectious enteritis/colitis: diarrhea, fever, and positive stool cultures. …”
Section: Methodsmentioning
confidence: 99%